Digital Anarchy and Security Dilemmas: Unraveling the TikTok Controversy in the Landscape of Cyber Realism and Hegemony Struggles between the United States and China - Permana, Aditya; Aurellie, Audrey (ARISTO, 2025)
This study delves into the intricate digital geopolitical dynamics surrounding the contentious relationship between TikTok and the United States (US) by employing the lens of cyber realism. The analysis focuses on the intricate interplay of digital anarchy, security dilemmas, and digital hegemony between the two entities. TikTok, originating from a Chinese company, faces scrutiny due to perceived threats to security and privacy. Within the framework of digital anarchy, characterized by the absence of a central governing authority in cyberspace, the TikTok case underscores the dynamic interplay of uncertainty and competition between US national interests and China’s quest for digital dominance. The dilemma faced by the US lies in the imperative to secure national interests while preserving freedom and innovation in the digital era. Amidst the pursuit of digital hegemony, the US aims to sustain its pivotal role in the digital landscape, interpreting TikTok’s expansion as a strategic move by China to extend influence and control over user data. Employing secondary data collection methods, including library research, this study reveals the US’s responses to these challenges, involving attempts to restrict TikTok’s operations within its borders, such as the ban on TikTok’s operation and endeavors to gain control of its US operations. However, subsequent revelations indicate the inaccuracy of the US’s allegations against TikTok.